2022
DOI: 10.3390/nano12091526
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Streptavidin on a Plasmonic Au-TiO2 Thin Film towards an LSPR Biosensing Platform

Abstract: Optical biosensors based on localized surface plasmon resonance (LSPR) are the future of label-free detection methods. This work reports the development of plasmonic thin films, containing Au nanoparticles dispersed in a TiO2 matrix, as platforms for LSPR biosensors. Post-deposition treatments were employed, namely annealing at 400 °C, to develop an LSPR band, and Ar plasma, to improve the sensitivity of the Au-TiO2 thin film. Streptavidin and biotin conjugated with horseradish peroxidase (HRP) were chosen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…According to the IUPAC definition [ 30 ], the LOD value was estimated in this case to be 1.339 RIU, corresponding to a 0.007 RIU shift from the water reference. The sensitivity of the nanoplasmonic membrane is similar to magnetron-sputtered nanocomposite thin film containing Au NPs dispersed on a titanium dioxide (TiO 2 ) matrix [ 7 ]. Apparently, the incorporation of the Au NPs on various solid matrices (i.e., chitosan and TiO 2 ) promotes the emergence of sensing ability, even at a considerably low RIS value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the IUPAC definition [ 30 ], the LOD value was estimated in this case to be 1.339 RIU, corresponding to a 0.007 RIU shift from the water reference. The sensitivity of the nanoplasmonic membrane is similar to magnetron-sputtered nanocomposite thin film containing Au NPs dispersed on a titanium dioxide (TiO 2 ) matrix [ 7 ]. Apparently, the incorporation of the Au NPs on various solid matrices (i.e., chitosan and TiO 2 ) promotes the emergence of sensing ability, even at a considerably low RIS value.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the incorporation of the Au NPs on various solid matrices (i.e., chitosan and TiO 2 ) promotes the emergence of sensing ability, even at a considerably low RIS value. In fact, Au-TiO 2 nanoplasmonic thin film, with sensitivity around ~33 nm/RIU, has been reported as a suitable sensing platform for biosensing detection [ 6 , 7 ]. In turn, Majdi et al [ 31 ] reported colloidal chitosan-gold nanoparticles with an established RIS value of 60 nm RIU −1 , determined by fitting of the LSPR band shift vs. the refractive index of several glycerol solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the functionalization of Au/TiO 2 thin films was reported, aiming at the production of sensitive LSPR-based optical transducers [36]. Streptavidin and biotin conjugated with horseradish peroxidase (HRP) were chosen as the model receptoranalyte to prove the efficiency of the immobilization method and to demonstrate the potential of the LSPR-based biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…Localized surface plasmon resonance (LSPR)-based sensors are a very promising type of optical biosensor for label-free detection. In another contribution, J. Borges et al developed a plasmonic Au-TiO 2 thin film and demonstrated its potential use as an LSPR platform for label-free biosensors [ 6 ]. Fluorescence-based detection is one of main sensing techniques, and S. J Park et al fabricated a nitrogen and phosphorus co-doped carbon dot/silver nanoparticle nanocomposite for a fluorescence sensor, which could sensitively detect metformin hydrochloride with high selectivity [ 7 ].…”
mentioning
confidence: 99%